2021
DOI: 10.21076/vizyoner.833838
|View full text |Cite
|
Sign up to set email alerts
|

Bankaların İçsel Pazarlama ve Pazar Odaklı Yaklaşımlarının Performans Üzerine Etkisi

Abstract: Information technologies are developing rapidly nowadays and globalization concept which shows up in parellel to IT has started to threaten the existence of firms by making competitive environment more intensive. Counter to this threat, businesses are trying to provide an advantage against their competitors by developing various of strategies. Internal marketing and market oriented approach are among the significant strategies which are developed within this scope. In the study, it is aimed to determine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This result is consistent with the study of Buchko et al (1998), which found that internal marketing increases employee creativity. It also overlaps with the findings of Ergün (2013), Can and Eskiler (2021), Beyaz, Güngör and Kılıçarslan (2021). Narcissistic leaders are happy with what they have, not what they produce.…”
Section: Conclusion and Discussionsupporting
confidence: 78%
“…This result is consistent with the study of Buchko et al (1998), which found that internal marketing increases employee creativity. It also overlaps with the findings of Ergün (2013), Can and Eskiler (2021), Beyaz, Güngör and Kılıçarslan (2021). Narcissistic leaders are happy with what they have, not what they produce.…”
Section: Conclusion and Discussionsupporting
confidence: 78%
“…This creates a measurable electrical conductance value. This electrical conductance can be measured by electrodes attached to two fingers [19].…”
Section: Gsr Signal Analysismentioning
confidence: 99%
“…Continuous contact of the electrodes with the fingers of the user is provided by a cover. A low voltage is applied to the skin to measure resistance, and the current delivered by the skin is measured [19].…”
Section: Gsr Signal Analysismentioning
confidence: 99%